Perspective: Implications of the COVID-19 Pandemic for Family-Focused Practice With Parents With Mental Illness and Their Families - Obradovic, Angela; Nicholson, Joanne (Frontiers in Psychiatry, 2022)
The goal of this perspective piece is to suggest challenges to family-focused practice with parents with mental illness and their children that have emerged during the COVID-19 pandemic. We discuss implications for practice, policy, and research that will benefit from rigorous study in the future, as we sift through lessons learned. The impact of the pandemic on the mental health and well-being of people around the world has been documented. Common adaptations in service delivery have included a shift to telehealth and digital tools. The pandemic has posed challenges to practice across the EASE Framework components for family-focused practice (i.e., Engage, Assess, Support and Educate) for both parents/families and practitioners. Governmental policy and funding responses will be critical to addressing the impact of stresses, disruptions and losses endured during the past months. Pandemic experiences and consequences have implications for research measures, methods, and outcomes, given the dramatic changes in people’s lives and the contexts in which they live. The shift to research implementation in virtual environments has resulted in challenges in maintaining confidentiality, and the privacy and security of data. As we move forward, it will be important to acknowledge the remaining uncertainty about the future and accommodate the profound changes in family life, professional practice, and research implementation related to the pandemic in our efforts to demonstrate the effectiveness of positive lessons learned while developing new approaches for dealing with the negative consequences of the pandemic.